Effectiveness of EU Directives in National Courts – Judicial Dialogue Continues: The Court of Justice’s Judgment in C-545/17 Pawlak (Polish Yearbook of International Law, 2021)
This commentary on the Court of Justice’s ruling in the Pawlak case concentrates on questions of the judicial application of EU law, in particular EU Directives. On the basis of the recent jurisprudence of the Court the authors present three issues: 1) the incidental effects of EU law for the procedural provisions of Member States; 2) the inability to rely on an EU directive by a member state’s authority in order to exclude the application of national provisions which are contrary to a directive; 3) the limits of the duty to interpret national law in conformity with EU law from the perspective of the Court of Justice and the referring court. Further, the article presents the judicial practice of the Polish Supreme Court, and in particular the follow-up decision of this Court not only taking into the account the ruling of the ECJ but also showing how the limitation of a conforming interpretation can be overcome in order to give full effect to EU law. In the authors’ view, this case is worth noting as an example of judicial dialogue in the EU.